Optical Vortex Brillouin Laser. Issue 4 (5th February 2023) - Zeng, Xinglin; Russell, Philip St. J.; Chen, Yang; Wang, Zheqi; Wong, Gordon K. L.; Roth, Paul; Frosz, Michael H.; Stiller, Birgit
Abstract: Optical vortices, which have been extensively studied over the last decades, offer an additional degree of freedom useful in many applications, such as optical tweezers and quantum control. Stimulated Brillouin scattering (SBS), providing a narrow linewidth and a strong nonlinear response, has been used to realize quasi‐continuous wave lasers. Here, stable oscillation of optical vortices and acoustic modes in a Brillouin laser based on chiral photonic crystal fiber (PCF) is reported, which robustly supports helical Bloch modes (HBMs) that carry circularly polarized optical vortex and display circular birefringence. A narrow‐linewidth Brillouin fiber laser that stably emits 1st‐ and 2nd‐order vortex‐carrying HBMs is implemented. Angular momentum conservation selection rules dictate that pump and backward Brillouin signals have opposite topological charge and spin. Additionally, it is shown that when the chiral PCF is placed within a laser ring cavity, the linewidth‐narrowing associated with lasing permits the peak of the Brillouin gain that corresponds to acoustic mode to be measured with resolution of 10 kHz and accuracy of 520 kHz. The results pave the way to a new generation of vortex‐carrying SBS systems with applications in optical tweezers, quantum information processing, and vortex‐carrying nonreciprocal systems. Abstract : Stable oscillations of optical vortices and acoustic modes in a Brillouin laser are demonstrated for the first time based on chiral photonic crystal fiber, which robustly supports helical Bloch modes that carry circularly polarized optical vortex and display circular birefringence. Topology‐selective stimulated Brillouin scattering effect dictates that the lasing vortex modes can be externally selected by pumping the appropriate mode.